Trichilemmal cystis in metastatic melanoma: a case report - Savarese, I.; Grazzini, M.; Gori, A.; D’Errico, A.; Doni, L.; Scarfì, F.; Covarelli, P.; Di Costanzo, F.; De Giorgi, V. (Experimental Oncology, 2017)
The malignant melanoma is a neoplasm associated with a wide variety of cutaneous paraneoplastic syndromes, as dermatomyositis, systemic sclerosis, paraneoplastic pemphigus. We describe a case of four multiple trichilemmal cystis arising on frontal region in the same patient with brain metastasis and unknown primary melanoma and discuss their relationship.